Surgical caseload and the risk of surgical Never Events in England - Moppett, I.K.; Moppett, S.H. (Wiley, 2015)
Never Events are medical errors that are believed to be preventable with appropriate measures. We surveyed all English acute NHS trusts to determine the number of surgical Never Events and surgical caseload for 2011–2014. There were 742 surgically related Never Events in three years, with no change in the number annually. The risk of a surgical Never Event was 1 in 16 423 operations (95% CI 1 in 15 283 to 1 in 17 648) or 1 Never Event per 12.9 operating theatres per year (95% CI 1 in 12.1 to 1 in 13.9). The risk of severe harm due to a Never Event was approximately 1 in 238 939 operations. There was no meaningful association between number of Never Events and other safety indicators. Surgical Never Events are undoubtedly important to individual patients, but they are not a useful metric to judge quality of care.